Patterns of Immunogenicity of an Inactivated Hepatitis A Vaccine in Anti-HIV Positive and Negative Hemophilic Patients - Santagostino, E; Gringeri, A; Rocino, A; Zanetti, A; de Biasi, R; Mannucci, P M (Thrombosis and Haemostasis, 1994)
Hepatitis A vaccination has been recommended to patients with hemophilia since they are exposed to potentially infectious clotting factor concentrates. Aim of this study was to assess the immunogenicity of vaccination in hemophiliacs, infected or not with the human immunodeficiency virus (HIV). A formalin-inactivated hepatitis A vaccine was injected subcutaneously to 113 susceptible adults and children and repeated after 1 and 6 months. 47 vaccinees were anti-HIV positive (28 asymptomatic, 15 with CD4 cell counts of less than 200/pl and 4 with symptomatic disease). The first dose of vaccine induced seroconversion, with antibody titers of at least 20 mlU/ml, in 89% of the 66 anti-HIV negative patients, 100% of them responding after the second injection. In anti-HIV positive hemophiliacs seroconversion rates and antibody titers were significantly lower than in non-infected patients. After 12 months, only 76% of anti-HIV positive vaccinees and 40% of those with signs of HIV disease progression maintained the antibody, whereas all anti-HIV negative patients had titers of 20 mlU/ml or more. Our results indicate that there is an association between defective response to hepatitis A vaccine and stage of progression of HIV disease.